2015
DOI: 10.1002/advs.201400018
|View full text |Cite
|
Sign up to set email alerts
|

Pure Single‐Crystalline Na1.1V3O7.9 Nanobelts as Superior Cathode Materials for Rechargeable Sodium‐Ion Batteries

Abstract: Pure single‐crystalline Na1.1V3O7.9 nanobelts are successfully synthesized for the first time via a facile yet effective strategy. When used as cathode materials for Na‐ion batteries, the novel nanobelts exhibit excellent electrochemical performance. Given the ease and effectiveness of the synthesis route as well as the very promising electrochemical performance, the results obtained may be extended to other next‐generation cathode materials for Na‐ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 72 publications
3
68
0
2
Order By: Relevance
“…[1][2][3][4][5] Owing to the much larger size of the sodium ion compared with the lithium ion, the identification of a suitable intercalation electrode material that can ensure reversible intercalation/extraction of sodium ions without an apparent volume change or structural degradation has been long pursued. [6][7][8] Amorphous iron phosphates have been identified as a promising cathode material for SIBs in view of their unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Owing to the much larger size of the sodium ion compared with the lithium ion, the identification of a suitable intercalation electrode material that can ensure reversible intercalation/extraction of sodium ions without an apparent volume change or structural degradation has been long pursued. [6][7][8] Amorphous iron phosphates have been identified as a promising cathode material for SIBs in view of their unique properties.…”
Section: Introductionmentioning
confidence: 99%
“…For linear dielectrics, J = 1/2DE = 1/2ε r ε 0 E 2 , where ε r is the dielectric constant of the ceramic materials and ε 0 is the vacuum permittivity [12][13][14][15][16][17]. Therefore, J strongly depends on the ε r and E, where E is limited by the breakdown strength (E b ).…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al have demonstrated single-crystalline Na 1.1 V 3 O 7.9 nanobelt cathodes for SIBs between 1.5 and 3.8 V, which exhibit superior electrochemical performances, including high specific capacity of 173 mA h g −1 , good cycle stability and rate capability, and high Coulombic efficiency. [66] The use of layered Na 2 MO 3 represents a viable strategy for enhancing the specific capacity due to there being a more than one electron process, an instance of a layered Na 2 RuO 3 showed reversible Na-ion insertion/extraction with capacity of 147 mA h g −1 (larger-than-one electron capacity of 137 mA h g −1 ) at 2.8 V vs Na/Na + and no capacity loss occurred during 20 cycles. [68] NaCrO 2 as a SIB cathode has a high theoretical redox capacity of 250 mA h g −1 based on the redox reaction of the Cr 6+ / 3+ couple.…”
Section: Single Transition-metal Oxidesmentioning
confidence: 99%
“…[93,94] A novel P2-O3 Na 0. 66 , good rate capability (134 mA h g −1 at 1C), and good cycling stability (84% retention after 50 cycles at 0.2C), as well as a largest energy density of approximately 640 W h kg −1 with 3.2 V for SIBs. [95] …”
Section: Mixed-cation Oxidesmentioning
confidence: 99%
See 1 more Smart Citation